2003
DOI: 10.1191/0960327103ht342oa
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aflatoxin B1 on the development of kwashiorkor in mice

Abstract: Seventy Swiss albino mice (6-week-old male) were selected for the investigation into aflatoxin B1's role in the cause of kwashiorkor. The mice were divided randomly into four groups. They were grouped within each group by being fed either low or normal protein level diets supplemented with very small amounts of aflatoxin B1 (0.5 mg/day). The control groups were fed aflatoxin B1-free diets containing either normal or low protein levels. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
(13 reference statements)
0
8
1
Order By: Relevance
“…The binding of aflatoxin to chromatin and DNA decreased by only 28–30% in rats with restricted food intake, while rats fed a restricted and protein‐deficient diet had aflatoxin binding to chromatin, DNA and chromatin protein decreased by 68, 72 and 66% respectively, suggesting that manipulation of protein content can affect the metabolism of AFB 1 . These observations are contradictory to some studies which found that a low‐protein diet worsened aflatoxicosis in rats . The possible explanation is that a low‐protein diet prevents hepatic macromolecular binding by altering the activity of mixed function oxidase which is involved in the metabolism of aflatoxin .…”
Section: Effect Of Protein On Aflatoxicosis (Table 2)contrasting
confidence: 66%
See 1 more Smart Citation
“…The binding of aflatoxin to chromatin and DNA decreased by only 28–30% in rats with restricted food intake, while rats fed a restricted and protein‐deficient diet had aflatoxin binding to chromatin, DNA and chromatin protein decreased by 68, 72 and 66% respectively, suggesting that manipulation of protein content can affect the metabolism of AFB 1 . These observations are contradictory to some studies which found that a low‐protein diet worsened aflatoxicosis in rats . The possible explanation is that a low‐protein diet prevents hepatic macromolecular binding by altering the activity of mixed function oxidase which is involved in the metabolism of aflatoxin .…”
Section: Effect Of Protein On Aflatoxicosis (Table 2)contrasting
confidence: 66%
“…GSH, for example, protects tissues from AFB 1 oxidative damage or acts as a cofactor for enzymatic detoxification of aflatoxin, but its level was reduced in protein‐malnourished rats exposed to AFB 1 . Besides, severe fatty infiltration, biliary proliferation and necrosis were observed in Swiss male albino mice fed a low‐protein diet and AFB 1 . In addition, mice fed the low‐protein diet and AFB 1 had a significantly higher concentration of alanine aminotransferase (ALT) (71 ± 38 IU dL −1 ) compared with those fed the low‐protein diet alone (45 ± 20 IU dL −1 ) .…”
Section: Effect Of Protein On Aflatoxicosis (Table 2)mentioning
confidence: 99%
“…The body performance data in the present study greatly agreed with the data reports of many other investigators. Weight loss as compared to control animals owing to aflatoxin treatment has been reported in rabbits, 24 mice 25 and rats. 26 Adedara et al 27 have reported a 12% body weight loss in mice treated with aflatoxin.…”
Section: Discussionmentioning
confidence: 99%
“…7,[20][21][22][23][24] Although the exact mechanisms of AF-induced growth stunting are not well-defined at this time, animal studies have indicated that AF exposure results in decreased weight gain, lowered feed conversion efficiency, vitamin depletion, and inhibited protein synthesis. [25][26][27][28][29][30][31][32][33][34][35] As a result of these epidemiological studies, it is clear that intervention strategies directed at the mitigation of child exposures are needed in areas where risk of AF consumption is high and malnutrition is common.…”
Section: Introductionmentioning
confidence: 99%